2018
DOI: 10.1371/journal.pone.0204619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the temporal and situational consistency of personality traits in adult dairy cattle

Abstract: Recent research suggests that personality, defined as consistent individual behavioral variation, in farm animals could be an important factor when considering their health, welfare, and productivity. However, behavioral tests are often performed individually and they might not reflect the behavioral differences manifested in every-day social environments. Furthermore, the contextual and longer-term temporal stability of personality traits have rarely been investigated in adult dairy cattle. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 61 publications
(81 reference statements)
2
25
0
Order By: Relevance
“…The underlying structure of the behavioural responses to each of the novelty tests comprised two main PCA components, which we interpreted as reflecting the personality traits 'boldness' and 'explorationactivity'. These traits have also been identified in dairy calves [20,22,24] and cows [21,31] with reasonable temporal stability using similar tests (although see [32] reporting low stability of behaviours in novelty tests over a short period of 1-3 weeks in calves). In our study, the 'boldness' trait had similarly high loadings for behaviours related to approach and contact with the novel human and object across the early (pre-to post-weaning) and later (puberty to lactation) periods of development; this suggests high royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The underlying structure of the behavioural responses to each of the novelty tests comprised two main PCA components, which we interpreted as reflecting the personality traits 'boldness' and 'explorationactivity'. These traits have also been identified in dairy calves [20,22,24] and cows [21,31] with reasonable temporal stability using similar tests (although see [32] reporting low stability of behaviours in novelty tests over a short period of 1-3 weeks in calves). In our study, the 'boldness' trait had similarly high loadings for behaviours related to approach and contact with the novel human and object across the early (pre-to post-weaning) and later (puberty to lactation) periods of development; this suggests high royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Discussionmentioning
confidence: 73%
“…The 'exploration-activity' trait had more moderate structural consistency over time, because high loadings were typically observed for at least two of the exploratory, locomotion, inactivity or attentive behaviours, but not necessarily the same behaviours across all periods. Foris et al [21] found moderate stability of 'boldness/shyness' trait, and weak stability of 'exploratory/ activity' trait in dairy cattle over a period of six months during lactation, which may be because the novel PCA coordinates (pre-weaning) PCA coordinates (post-weaning) -…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that animals only formed clusters within the specific animal and showed only little social stability within the herd structure. Contrarily, Foris et al [ 84 ] demonstrated that cows formed relatively stable contact networks, and that these contact networks can influence the individual cows reactions within the group [ 85 ]. ML could offer the opportunity to continuously monitor the stability of such groups and their effect on affective state or physiological parameters.…”
Section: Resultsmentioning
confidence: 99%
“…On d41, 60 and 79, a novel person test, which is a new method adapted from previous studies that expose both wildlife [19,20] and domestic species [21,22] to novel objects, and avoidance test were conducted on cattle while in their home pens, between 0730-1100hr. Prior to the novel person test, three Inca 4K Action Cameras were placed on pen corners and left to film for 10min, with this footage analysed with a species-specific ethogram capturing posture and activity.…”
Section: Methodsmentioning
confidence: 99%